Pengelolaan Pelatihan Ketenagakerjaan Di Balai Besar Latihan Kerja Industri Surakarta - Sri Irwanto, Wahyu (Kiat Bisnis, 2012)
The purpose of this study was to describe (1) the characteristics of the training program in the Center for Industrial Training Surakarta. (2) the characteristics of the training infrastructure in the Great Hall of the Industrial Training Surakarta. (3) characteristics of the implementation of training programs in the Center for Industrial Training Surakarta. Type of research is a qualitative research, ethnographic research design. Data collection techniques using in-depth interviews, participant observation method and the method of documentation. The analysis in this study is to use cross-site analysis model. The timing of the custom-tailored training, for this kind of basic instructor training program conducted for 7 months, PBK program dilaksanan range 1-3 months, and upgrading program implemented about 1 month.Â Keywords: management; employment; training.